Responda a seguinte Expressão Numérica .
![(5 {}^{2} - 3 \times 7) + ( \sqrt[]{}49 + 3 \times 2) \times 2 - 2 {}^{3} = (5 {}^{2} - 3 \times 7) + ( \sqrt[]{}49 + 3 \times 2) \times 2 - 2 {}^{3} =](https://tex.z-dn.net/?f=%285+%7B%7D%5E%7B2%7D+-+3+%5Ctimes+7%29+%2B+%28++%5Csqrt%5B%5D%7B%7D49++%2B+3+%5Ctimes+2%29+%5Ctimes+2+-+2+%7B%7D%5E%7B3%7D+%3D+)
Soluções para a tarefa
Respondido por
1
de acordo com o enunciado vem:
25 - 21 = 4
7 + 6 = 13
13 * 2 = 26
-2^3 = -8
= 4 + 26 - 8 = 22
Perguntas interessantes
Biologia,
10 meses atrás
Ed. Física,
10 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás